2021
DOI: 10.1155/2021/8864655
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Reactivation Potential Risk Factors in Hepatocellular Carcinoma via Transcatheter Arterial Chemoembolization: A Retrospective Research

Abstract: Background. To explore the clinical characteristics of reactivation of hepatitis B virus (HBV) in hepatocellular carcinoma (HCC) after transcatheter arterial chemoembolization (TACE). The pathological correlation of prognosis and hepatitis B virus reactivation has been given detailed analyses in our research. Methods. A total of 108 related TACE-treated HCC clinical data from January 2008 to January 2016 was gleaned and involved in this retrospective analysis. To lucubrate the nuance of survival rates between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…HBV reactivation was defined as an increase of serum HBV DNA > 1 log or reappearance of HBV DNA in patients with undetectable HBV DNA at baseline in 33 studies, [ 19–21,23–30,32–36,38–43,45–48,50–53,56–58 ] while this definition varied in five studies [ 31,44,49,55,59 ] and was not clearly provided in the remaining three studies. [ 22,37,54 ] A definition of HBV‐related biochemical reactivation was not provided in 18 studies, [ 21–27,30,32–34,37–41,54,59 ] while it varied widely among the remaining 23 studies. [ 19,20,28,29,31,35,36,42–53,55–58 ] Only increases in aminotransferase levels attributed to HBV reactivation by the authors were considered HBV‐related biochemical reactivation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HBV reactivation was defined as an increase of serum HBV DNA > 1 log or reappearance of HBV DNA in patients with undetectable HBV DNA at baseline in 33 studies, [ 19–21,23–30,32–36,38–43,45–48,50–53,56–58 ] while this definition varied in five studies [ 31,44,49,55,59 ] and was not clearly provided in the remaining three studies. [ 22,37,54 ] A definition of HBV‐related biochemical reactivation was not provided in 18 studies, [ 21–27,30,32–34,37–41,54,59 ] while it varied widely among the remaining 23 studies. [ 19,20,28,29,31,35,36,42–53,55–58 ] Only increases in aminotransferase levels attributed to HBV reactivation by the authors were considered HBV‐related biochemical reactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies including 3474 patients who underwent TACE for HCC provided data for HBV reactivation, which was diagnosed in 517 (14.9%) patients (pooled estimate, 19%, 95% CI, 13%–26%; heterogeneity, p < 0.01) (Table 1 and Figure 4A). [ 19,20,35–43,58 ] The pooled rates of HBV reactivation were higher in 2296 patients who received no prophylactic NA (pooled estimate, 23%; 95% CI, 17%–30%; heterogeneity, p < 0.01) (Figure 4B) [ 19,20,35–43,58 ] than in 1178 patients who did (pooled estimate, 1%; 95% CI, 0%–10%; heterogeneity, p = 0.13) (Figure 4C). [ 35,38–40,43,58 ] The pooled rates of HBV reactivation were 16% (95% CI, 10%–23%; heterogeneity, p < 0.01) in seven studies with mean/median follow‐up ≤6 months [ 20,35,36,39,41,43,58 ] and 23% (95% CI, 11%–42%, heterogeneity, p < 0.01) in three studies with mean/median follow‐up >6 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [ 99 ] reported that HBV DNA-negative patients with HCC still had a risk of HBV reactivation after TACE. Wang et al [ 100 ] reported that HBV reactivation after TACE is an independent prognostic factor and a crucial reason for a poor prognosis and lower survival rate of patients with HCC. However, Xu et al [ 96 ] reported that TACE could decrease the HBV DNA level in patients with HCC.…”
Section: Several Issues That Deserve Further Studymentioning
confidence: 99%